Science of successful living - "Welgos, James" (Middlesex, 1957)
This book presents the view that men and women possess the psycho-cybernetic or self-governing, goal-seeking and goal-achieving faculties of the Evolutionary Law of the Universe. These cybernetic faculties can be used at individual and collective or national levels. In actuality, these faculties have to be nurtured and used effectively for the successful evolution and consequent successful living by the people. The book presents a holistic model for managing the evolution of people towards successful living. This holistic management of people's evolution is advocated in the book as good governance and the science of successful living.
Keywords: Psychology